Alternative conceptions and students’ achievement in basic science and technology: Evidence from upper basic education - Johnson Mhile Yaapera; Terungwa James Age (CV. FOUNDAE, 2026)
Background: In science education, students are expected to develop an understanding of concepts, principles, and scientific reasoning. However, many learners enter the classroom with pre-existing alternative conceptions shaped by their everyday experiences. These prior understandings may not always align with scientific explanations and can influence how students engage with and interpret new knowledge in Basic Science and Technology. Aims: Building on this concern, the present study examined the relationship between alternative conceptions and students’ achievement in Basic Science and Technology among Upper Basic Education learners. Method: To address this aim, an ex-post facto descriptive research design was employed. A total of 398 Upper Basic Education 1 students were selected from three educational zones in Benue State, Nigeria. Data were collected using the Basic Science Alternative Conceptions Identification Checklist and the corresponding achievement test. The data were analyzed using frequency counts, percentages, mean, standard deviation, and t-test at a 0.05 level of significance. Results: The analysis indicated that students held alternative conceptions across multiple Basic Science concepts. These conceptions were found to have a significant negative influence on students’ achievement. In addition, the findings revealed no significant difference in the influence of alternative conceptions on achievement between male and female students. Conclusion: Overall, the study highlights that alternative conceptions remain prevalent among Upper Basic Education students and play a significant role in shaping their achievement in Basic Science and Technology. Addressing these conceptions through appropriate instructional strategies is therefore essential for improving students’ learning outcomes.